Passive Immunotherapy of Cynomolgus Monkeys with Anti-Rotavirus IgY - Gentil Arthur Bentes; Juliana Rodrigues Guimarães; Eduardo de Mello Volotão; Natália Maria Lanzarini; Alexandre dos Santos da Silva; Noemi Rovaris Gardinali; Renato Sergio Marchevsky; José Paulo Gagliardi Leite; Jaqueline Mendes de Oliveira; Marcelo Alves Pinto (MDPI AG, 2024)
Immunoglobulins Y (IgY) purified from egg yolks of hens represents an attractive, cost-effective alternative for the development of new diagnostic and therapeutic platforms. In this study, we evaluated the therapeutic efficacy of rotavirus-specific IgY in a cynomolgus monkey (Macaca fascicularis) model. Animals were experimentally infected with human rotavirus Group A (RVA), the most common cause of severe acute diarrhoea among young children worldwide. Animals were administered human RVA (3.1 × 107 FFU/mL) by oral gavage, challenged with 2.5 mg of anti-RVA IgY orally, and monitored for five days according to clinical, haematological and biochemical parameters; serum electrolyte levels; viral shedding; and histopathological changes. Immunotherapy with anti-RVA IgY had a protective effect against severe rotavirus-induced enteritis in four of the ten treated monkeys, as evidenced by histopathological findings. Although only one animal had diarrhoea, all but one exhibited virus shedding regardless of the treatment.